The thrombolytic and cytotoxic effects of nigella sativa (L.) seeds: the prophetic medicine - Babar, Z.M.; Jaswir, Irwandi; Maifiah, Mohd Hafidz Mahamad; Ismail, Soraya; Raus, Raha Bt. Ahmad; Tareq, A. M.; Ahfter, F.; Faraque, A.; Ali Reza, A.S.M; Sayeed, M. A.; Hossain, Md. M.; Uddin, M.; et al. (Egyptian Society of Sciences and Halal Products, 2020)
The Water-Soluble Extract (WSE) is a crude bioactive phytoconstituent of Nigella sativa (L.) seeds discovered recently. The current findings report about the thrombolytic and cytotoxic effects of WSE using human blood clot lysis and brine shrimp lethality (BSL) bioassay. The thrombolytic effect of WSE (1,666.67 µg/mL) was determined via the clot and lysate weight measurements compared to streptokinase (STK) of 30,000 IU/mL and normal saline (NS) while the cytotoxicity of WSE (44.14-2,000 µg/mL) against vincristine sulfate (VCS;3.125-100 µg/mL). WSE has shown extremely statistically significant (p<0.0001) clot lysis (90.00%) compared to NS (3.76%) whilst it was also significantly different (p<0.0063) to STK (72.41%) exhibiting LC50 of 1,795.90 µg/mL vs. VCS (39.25 µg/mL) in a dose-dependent manner. The current results suggested WSE has a potent thrombolytic effect with mild dose-dependent cytotoxicity towards brine shrimp nauplii (Artemia salina). It also suggested WSE might have enzymatic roles on thrombin, fibrin, and plasmin of blood. This pharmacological action of WSE is might be due to its antioxidant property, short-chain fatty acids and/or amino acids. Further studies are highly recommended on the enzymatic role(s) and bioactive phytoconstituents of WSE.